1998
DOI: 10.1104/pp.118.4.1517
|View full text |Cite
|
Sign up to set email alerts
|

Phytochrome Regulates Gibberellin Biosynthesis during Germination of Photoblastic Lettuce Seeds

Abstract: Germination of lettuce (Lactuca sativa L.) seed is regulated by phytochrome. The requirement for red light is circumvented by the application of gibberellin (GA). We have previously shown that the endogenous content of GA 1 , the main bioactive GA in lettuce seeds, increases after red-light treatment. To clarify which step of GA 1 synthesis is regulated by phytochrome, cDNAs encoding GA 20-oxidases (Ls20ox1 and Ls20ox2, for L. sativa GA 20-oxidase) and 3␤-hydroxylases (Ls3h1 and Ls3h2 for L. sativa GA 3␤-hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
171
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 223 publications
(184 citation statements)
references
References 35 publications
9
171
1
3
Order By: Relevance
“…For instance, light was shown to promote the germination of Arabidopsis and lettuce seeds by increasing their GA content via the induction GA 3b-hydroxylases (Toyomasu et al, 1998;Yamaguchi et al, 1998). Alabadí et al (2004) reported that both mutational and chemical disruption of GA synthesis can interfere with normal skotomorphogenesis and cause aberrant expression of light-regulated nuclear genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, light was shown to promote the germination of Arabidopsis and lettuce seeds by increasing their GA content via the induction GA 3b-hydroxylases (Toyomasu et al, 1998;Yamaguchi et al, 1998). Alabadí et al (2004) reported that both mutational and chemical disruption of GA synthesis can interfere with normal skotomorphogenesis and cause aberrant expression of light-regulated nuclear genes.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, most lightresponsive genes of GA synthesis were also found to be under wavelength-or photoreceptor-specific control. In Arabidopsis, lettuce (Lactuca sativa), and pea (Pisum sativum), light was shown to regulate the expression of GA 3b-hydroxylase and GA 20-oxidase isoforms via either phytochrome-dependent or -independent mechanisms (Toyomasu et al, 1998;Yamaguchi et al, 1998;Ait-Ali et al, 1999;Jackson et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…9). Expression of GA3ox genes in lettuce and Arabidopsis is well known to be photoreversibly regulated by light through phytochrome (Toyomasu et al, 1998;Yamaguchi et al, 1998). Understanding the cross talk between light and temperature signals on the regulation of GA3ox gene expression may give us insight into how plants transduce multiple signals and how plants respond to complex environmental stimuli.…”
Section: Suppression Of Ga Synthesis Is Critical For Thermoinhibitionmentioning
confidence: 99%
“…Light signals mediated by phytochromes are critical environmental determinants for photoblastic seed germination (Borthwick et al, 1952;Shinomura et al, 1996). GA levels are regulated by phytochrome in lettuce and Arabidopsis seeds, in which genes encoding GA 3-oxidase (GA3ox) and GA 2-oxidase (GA2ox) are regulated in a photoreversible manner (Toyomasu et al, 1998;Yamaguchi et al, 1998). In Arabidopsis, GA3ox1 and GA3ox2 are up-regulated and GA2ox2 is down-regulated by red light, which promotes seed germination.…”
mentioning
confidence: 99%
“…GA biosynthesis de novo is a prerequisite for germination because inhibitors of GA biosynthesis applied during imbibition effectively inhibit the process (Nambara et al, 1991;Derkx and Karssen, 1993). Arabidopsis seeds have a very low germination rate in the dark, while both light and cold promote seed germination, at least partially by stimulating GA biosynthesis (Derkx and Karssen, 1994;Toyomasu et al, 1998;Yamaguchi et al, 1998;Yamauchi et al, 2004). Furthermore, light and cold each have been shown to reduce expression of GA2ox2 (Yamauchi et al, 2004;Oh et al, 2006).…”
Section: Seed Germinationmentioning
confidence: 99%